1996
DOI: 10.1002/anie.199610841
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry‐Based Metal Complex Cluster Formation

Abstract: There are examples of non-covalently linked molecular clusters in nature of stunning symmetry and beauty. Two are shown in Figure 1. The 24 individual protein subunits of apoferritin['.21 (the elipsoid-shaped subunits on the left of Fig. 1) cluster Fig. 1. Models of theapoferritin 24-mer (left) and human rhinovirus 60-mer (right). The view of ferritin IS down one of the C, axes. the other two C, axes of the octahedral cluster are horizontal and vertical, respectively. Along the body diagonal (between three of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
0
10

Year Published

1998
1998
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 216 publications
(142 citation statements)
references
References 22 publications
4
128
0
10
Order By: Relevance
“…The behavior of these cage complexes contrasts with some recent examples described by Raymond and coworkers (10,17), based on bridging ligands whose two binding sites are carefully arranged to optimize cage formation. These ligands cannot act as tetradentate chelates to a single metal, because the binding sites are divergent and give M 4 L 6 cages quantitatively without the assistance of a template effect.…”
Section: Resultsmentioning
confidence: 64%
See 2 more Smart Citations
“…The behavior of these cage complexes contrasts with some recent examples described by Raymond and coworkers (10,17), based on bridging ligands whose two binding sites are carefully arranged to optimize cage formation. These ligands cannot act as tetradentate chelates to a single metal, because the binding sites are divergent and give M 4 L 6 cages quantitatively without the assistance of a template effect.…”
Section: Resultsmentioning
confidence: 64%
“…These ''adamantoid'' cages ( Fig. 1) were first described by and have since been studied by several other groups (17)(18)(19)(20)(21)(22)(23)(24)(25). A notable feature of many such complexes is that the central cavity can accommodate guest species, with the nature of the guest depending on the charge carried by the surrounding complex cage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…21 One of the first examples is a [Ga 4 (3) 6 ] (4) structure based on C 2 -symmetric bishydroxamate ligands 3 ( Figure 3). 44 1 H NMR studies showed 4 to exist in solution as a mixture of the T, C 3 , and S 4 diastereomers having ≡ Figure 1. The subcomponent self-assembly of an octahedral metal ion (M 2+ ), 2-formylpyridine and an amine (commonly an aromatic amine, as shown) leads to a chiral, octahedral metal complex with C 3 symmetry; such complexes can form the vertices of tetrahedral supramolecular structures.…”
Section: Stereochemistry Of Tetrahedral Metalorganic Capsulesmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, various metallamacrocycles have been studied as important building blocks in the construction of functional supramolecular materials that can be utilized for molecular recognition, selective transformation, drug delivery systems, catalysts, storage, and biomimics. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Facile synthetic methods are either the ring-expansion [21][22][23] by means of labile metalligand coordination or the ring-formation via appropriate tectonics.…”
Section: Introductionmentioning
confidence: 99%